2013
DOI: 10.1039/c3dt50612f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide release catalysed by electron transfer: electrochemical and spectroscopic investigations of [Re(bpy-R)(CO)4](OTf) complexes relevant to CO2 reduction

Abstract: [Re(bpy-tBu)(CO)4](OTf) (bpy-tBu = 4,4'-di-tert-butyl-2,2'-bipyridine, OTf = trifluoromethanesulfonate) (1) and [Re(bpy)(CO)4](OTf) (bpy = 2,2'-bipyridine) (2) were synthesized and studied as proposed intermediates in the electrocatalytic reduction of carbon dioxide (CO2) by Re(bpy-R)(CO)3X. Both compounds demonstrated increased current responses in cyclic voltammograms under CO2. Complex 1 was also characterized by X-ray crystallography. Infrared-spectroelectrochemistry (IR-SEC) of 1 and 2 indicated that upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
89
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 30 publications
6
89
0
Order By: Relevance
“…This increase did not correspond to a pre-existing redox feature (−2.17 V vs Fc/Fc + ), which suggests that product dissociation is rate-limiting, Figure 6. 40 The addition of 2,2,2-trifluoroethanol (TFE) as a proton source showed a further increase in the observed current under CO 2 , although returning to N 2 saturation showed a new irreversible redox feature at −2.79 V vs Fc/Fc + , indicative of proton reduction under these conditions. 54 …”
Section: Resultsmentioning
confidence: 96%
“…This increase did not correspond to a pre-existing redox feature (−2.17 V vs Fc/Fc + ), which suggests that product dissociation is rate-limiting, Figure 6. 40 The addition of 2,2,2-trifluoroethanol (TFE) as a proton source showed a further increase in the observed current under CO 2 , although returning to N 2 saturation showed a new irreversible redox feature at −2.79 V vs Fc/Fc + , indicative of proton reduction under these conditions. 54 …”
Section: Resultsmentioning
confidence: 96%
“…Scission of the C–OH bond in [Mn-CO 2 H] − assisted by TFE leads to [Mn-CO] 0 . CO evolution may occur spontaneously from [Mn-CO] 0 prior to one-electron reduction (Grice et al, 2013) and generation of [Mn] − . However, this mechanism is yet to be experimentally verified for this class of Mn catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Kubiak has tracked reduced intermediates and their reactivity toward CO 2 . 45 , 46 , 51 , 52 Ishitani has shown that the usual sacrificial reducing agent, triethanolamine (TEOA), coordinates to rhenium by deprotonation to form a rhenium alkoxide of the type ReOCH 2 CH 2 N(CH 2 CH 2 OH) 2 which can insert CO 2 to form a rhenium carbonate derivative. 53 Inoue et al have used mass spectrometry to study reduction of ReCl(4,4′dimethyl-2,2′-bipyridine)(CO) 3 with triethylamine.…”
Section: Introductionmentioning
confidence: 99%